Konsep Kurikulum Merdeka Belajar Ditinjau dari Pandangan Aliran Filsafat Pendidikan Progresivisme - Norma Yunaini; Nurulhuda Md Hassan; Agus Kichi Hermansyah; Rukiyati Rukiyati; Mulyo Prabowo (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study examines the concept of independent learning from the perspective of progressivism educational philosophy. The method used in this research is library research. The researcher reviewed various works of literature and then analyzed related to the Concept of Merdeka Belajar Curriculum in Elementary Schools from the Viewpoint of Educational Philosophy. Data collection techniques are conducted by including eligibility, screening, identification, and analysis from various sources such as books, articles, and relevant research results. The search for research data resulted in 5 electronic books and 36 articles from scholars. The texts studied included educational philosophy books and independent curriculum guides specific to elementary schools. In contrast, there are several selected articles. Articles found in the Sholer and Mendeley databases, using the search terms